Resin foraging dynamics in Varroa destructor‐infested hives: a case of medication of kin?. (21st November 2017) - Pusceddu, Michelina; Piluzza, Giannella; Theodorou, Panagiotis; Buffa, Franco; Ruiu, Luca; Bullitta, Simonetta; Floris, Ignazio; Satta, Alberto
Abstract: Social insects have evolved colony behavioral, physiological, and organizational adaptations (social immunity) to reduce the risks of parasitization and/or disease transmission. The collection of resin from various plants and its use in the hive as propolis is a clear example of behavioral defense. For Apis mellifera, an increased propolis content in the hive may correspond to variations in the microbial load of the colony and to a downregulation of an individual bee's immune response. However, many aspects of such antimicrobial mechanism still need to be clarified. Assuming that bacterial and fungal infection mechanisms differ from the action of a parasite, we studied the resin collection dynamics in Varroa destructor ‐infested honeybee colonies. Comparative experiments involving hives with different mite infestation levels were conducted in order to assess the amount of resin collected and propolis quality within the hive, over a 2‐year period (2014 and 2015). Our study demonstrates that when A. mellifera colonies are under stress because of Varroa infestation, an increase in the number of resin foragers is recorded, even if a general intensification of the foraging activity is not observed. A reduction in the total polyphenolic content in propolis produced in infested versus uninfested hives was also noticed. Considering that different propolis types show varying levels of inhibition against a variety of honey bee pathogens in vitro, it would be very important to study the effects against Varroa of two diverse types of propolis: from Varroa ‐free and from Varroa ‐infested hives.